Geophysical and structural survey in copper occurrence located in the northern region of the camaquã basin (rs) - Moreira, César Augusto [UNESP] (2021)
The geophysical diagnosis of mineral deposits can be extremely useful in detailing mineralized zones and is a strategy for direct sampling by probing holes for content analysis. This study involves the combined use of Electrical geophysical methods (DC resistivity and Induced Polarization), geological recognition and structural field analysis, with a study of the mineralized occurrence of copper, previously described in a systematic geochemical survey carried out by the Geological Survey of Brazil (CPRM), located in the north of the Camaquã Basin, extreme south of Brazil. The mineral occurrence is partially outcropped and consists of quartz vein shafts with malachite and relic structures of sulfides, contained in schist. Structural data obtained in the field revealed the existence of a system of fracture pairs in the directions N40-50W and N70-80E. Such information is presented in the programming of the geophysical data acquisition scheme, which consisted of 6 lines of electrical tomography with 410m each, in azimuthal disposition and Schlumberger arrangement, where all lines cross a single center and are separated according to an angle of 30°, in an attempt to cover fractures in various orientations. The 2D results reveal the existence of high chargeability zones (>40mV/V) positioned below the 40m depth. These data were interpolated in 3D visualization models and generated resistivity and chargeability maps for several depths, which integrated with previous structural data, and indicate the existence of zones with potential sulfide concentration with strong structural control, in addition to clear target recognition for direct and objective probing evaluation, with rationalization of costs.